Wybrane aspekty crowdsourcingu - Laska, Maciej (Selected Aspects of Crowdsourcing, 2007)
As recent studies have shown, more and more members of the business community of the Information Era make use not only of the Internet information resources, but also of the knowledge and professional skills of its users. This co-operation may take many diverse forms, and the phenomenon itself - when it refers to a permanent relationship between the company and given Internet community or communities - is usually defined as crowdsourcing. In this article the origin of this phenomenon was analyzed, as well as advantages that can be gained by the enterprise that effectively explores knowledge resources of the Internet societies. The author presented several interesting initiatives developed in the cyberspace, that are, on the one hand, an evidence of qualitative change in the operational use of the Internet and increasing creative productivity of its users, on the other - a chance to rationalize the cost structure of virtual enterprises.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (11); 2007; nr 1156, s. 169-180